(RETRACTED) INFORMATION LITERACY: AN ALTERNATIVE TO SUPPORT LEARNING OUTCOMES IN BIOLOGICAL STUDENTS - Sari, M S; Sunarmi, Sunarmi; Sulasmi, E S; Wicaksono, R S; Sudrajat, A K (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2019)
This paper is retracted by editor due to publication ethics missconducted by author (simultaneously publication in other journal).